TECHNOLOGIES OF PEDAGOGICAL INTERACTION: METHODS OF IMPLEMENTATION - I.V. Lovyanova (Academy of Cognitive and Natural Sciences, 2008)
In article on base of the analysis of innovative processes, occurring in formation, is determined essence and place technology in hierarchies notion: paradigm, model, methods, technology. As one of the first step on way to new technology is considered realignment mechanism pedagogical interaction.